Pendidikan Kesehatan Tentang Reproduksi Remaja Terhadap Pengetahuan dan Sikap pada Siswa SMK Pacet Kabupaten Mojokerto - Dwi Helynarti Syurandhari; Hari Kuswanto; Asih Media Yuniarti; Mukhammad Himawan Saputra (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
Adolescent problems regarding sexuality and reproductive health are felt to be increasingly complex and concerning. The increasing cases surrounding adolescent reproduction occur due to the incomprehension of adolescents to various aspects of reproduction related to themselves. The purpose of this study was to determine the effect of adolescent reproductive health counseling on knowledge and attitudes in students of SMK Pacet, Mojokerto Regency. This type of research is an experimental study using Pretest and Posttest (One Group Pretest And Posttest Design). The study population of 320 students was taken as a sample with the Stratified Random Sampling technique of 178 respondents. Univariate and bivariate analysis, non-parametric data distribution with Wilcoxon test. The results of the study were that most respondents had sufficient knowledge about adolescent reproductive health before being given counseling, most respondents had good knowledge about adolescent reproductive health after being given counselling. The results of the Wilcoxon test obtained the results of the Asymp.Sig value. (2- tailed) = 0.000, then it can be concluded that there is a significant influence between the knowledge of students of SMK Pacet Mojokerto Regency towards the intervention provided, namely adolescent reproductive health counseling. Schools can collaborate with several relevant agencies to jointly improve adolescent reproductive health counseling programs, as well as provide facilities and infrastructure such as additional media for student learning facilities such as providing several leaflets related to reproductive health, so that they can be used to increase student knowledge.